Pengaruh Perhatian Orang Tua Dalam Upaya Meningkatkan Prestasi Belajar BTQ Di RA An-nur Al-masturiah - Ai Yani Mulyani; Asep Munajat; Alfian Ashshidiqi (Tunas Siliwangi, 2024)
Problems related to the fact that children have not memorized hijaiyah letters at all, therefore researching to find the cause whether there is an influence of parental attention on their children’S BTQ learning achievement. This research method is a field research method with a quantitative approach, the researchers use is quai-eksperimental. The population in this study amounted to 46 children and the sample in this study were 30 children. Data collection techniques in this study are by using obsevation, documentation, quistionnaires. The data analysis technique used in this research is simple linear regression. From the results of research and data analysis it can be concluded that there is a significant regression in parental attention in an effort to improve children’s BTQ learning achievement. > f table or 0,539 > 0,433 then Ho rejected (significant regression) while Ha is accepted (insignificant regression).